The success of the AESM experiment on the organization of the doctoral school - Eugenia FEURAŞ (Eastern European Journal of Regional Studies)
This article presents the results of the experiment on the organization and functioning of the doctoral school of AESM, founded by AESM in 2011. These results show the evolution of the PhD candidates’ competencies, acquired over the period of doctoral studies, the satisfaction level of the knowledge obtained in the compulsory and optional subjects, the opinion of the PhD candidates regarding the fulfillment of the contract terms by the PhD supervisors and candidates themselves, PhD students’ work intensity and their international mobility, etc. The survey results show the high efficiency of doctoral studies organized within the present regulatory framework, according to the European models and good practices.